Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.cmi.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Proposed primary endpoints for use in clinical trials that compare treatment options for bloodstream infection in adults: a consensus definition

Abstract: No standardised endpoint definitions exist to aid the design of trials that compare antibiotic therapies for bloodstream infection (BSI). We reviewed endpoints used in contemporary BSI studies and defined consensus endpoints using a modified Delphi process. Prospective studies, randomised trials or registered protocols comparing antibiotic therapies for BSI, published from 2005 to 2016, were reviewed. Different primary and secondary endpoints were defined for pilot (small-scale studies designed to evaluate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 41 publications
(13 reference statements)
0
55
0
Order By: Relevance
“…The binary outcome of 90-day survival was chosen to reflect the recognized outcome measures of bacteremia trials [10]. …”
Section: Methodsmentioning
confidence: 99%
“…The binary outcome of 90-day survival was chosen to reflect the recognized outcome measures of bacteremia trials [10]. …”
Section: Methodsmentioning
confidence: 99%
“…Mortality endpoints are not very sensitive, while clinical cure endpoints are subjective, microbiological cure is not viable, and antibiotic- or ventilation-free days are ambiguous (Table 2). It will not be easy to reach consensus, but Delphi processes like the one recently published on endpoints for BSIs [3] are a step in the right direction. In this review, the authors concluded that it is unlikely for one endpoint to capture all relevant information and proposed to use composite endpoints.…”
Section: Possible Solutions (And Their Potential Shortcomings)mentioning
confidence: 99%
“…In two recent systematic reviews [3, 9], it is proposed to combine mortality and microbiological endpoints for BSIs, and mortality and clinical cure for HAP/VAP, respectively. However, both groups agree more debate is required to improve definitions of clinical cure and to finalize discussions on the importance of patient-centered outcomes versus microbiological or clinical response, as well as the role of safety endpoints.…”
Section: Components Of Composite Endpointsmentioning
confidence: 99%
See 2 more Smart Citations